PENGARUH KUALITAS DAYA TARIK WISATA TERHADAP TINGKAT KEPUASAN WISATAWAN, STUDI KASUS DI WADUK JATILUHUR - KABUPATEN PURWAKARTA - Darsono, Rahmat (JURNAL NASIONAL PARIWISATA, 2013)
This research was conducted to find out how it influences the quality of tourist attraction (Accessibility, Attractions, Amenities, Activities, Available packages, Ancillary services) towards the satisfaction of tourists who come to the Jatiluhur Reservoir in Purwakarta Regency. By taking a sample of the tourists who visit the Jatiluhur can be examined that factors such as Accessibility has a value of 2,357, Attractions -4,173, 0,408 Amenities, Activities - 4,457, Available packages 6,391, Ancillary services 5,110.Based on the research, the correlation coefficient, value (r) of 0.9, this means that the relationship between the qualities of the tourist attraction of tourist satisfaction Jatiluhur is very strong. In the meantime, the coefficient of determination is 81%. Does that mean that satisfaction is affected by tourist attraction of 81%. The rest of 19% is affected by other factors which are not examined in this reserach.